2015
DOI: 10.1111/jnc.13095
|View full text |Cite
|
Sign up to set email alerts
|

Receptive range analysis of a mouse odorant receptor subfamily

Abstract: Mammals deploy a large array of odorant receptors (ORs) to detect and distinguish a vast number of odorant molecules. ORs vary widely in the type of odorant structures recognized and in the breadth of molecular receptive range (MRR), with some ORs recognizing a small group of closely related molecules and other ORs recognizing a wide range of structures. While closely related ORs have been shown to have similar MRRs, the functional relationships among less closely related ORs are unclear. We screened a small g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…This is corroborated by previous studies reporting that phylogenetically related mouse ORs had overlapping odorant specificities. 66,67 Another compound that was found in wolf urine and initially has been considered to be fear-inducing is 2,6-DMP. 9 In further tests by Osada et al (2011), this particular compound, however, failed to significantly induce fear reactions-its status as a semiochemical, thus, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This is corroborated by previous studies reporting that phylogenetically related mouse ORs had overlapping odorant specificities. 66,67 Another compound that was found in wolf urine and initially has been considered to be fear-inducing is 2,6-DMP. 9 In further tests by Osada et al (2011), this particular compound, however, failed to significantly induce fear reactions-its status as a semiochemical, thus, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence-based approaches to response prediction require a reasonably high homology among the receptors. In vertebrates, receptors with less than 40% sequence identity were found to have little overlap in their responses (Li et al 2015). The insects ORs presented a particularly difficult test case as they have only about 20 % homology among conspecific ORs; indeed, we found that there was no correlation between the overall sequence similarity and the response similarity among the ORs.…”
Section: Discussionmentioning
confidence: 64%
“…Finally, this phylogenetic tree indicates a tendency of bidirectional diversion among the 114 18kb-haplotypes. By analyzing twenty six 1KGP populations together (thousands of haplotypes), a much stronger bidirectional diversion of the 18kb promoter was observed (without geographic correlation, data not shown), validating the COGA subjects-based finding and implying again a functional correlation between genetics of the SLC6A3 promoter and related phenotypes[103].…”
Section: Discussionmentioning
confidence: 52%